The Local Government Strategies in Building Halal Tourism in Bener Meriah Regency - Rahmat Yanidin; Muhammad Bin Abubakar; M Akmal (Malikussaleh Social and Political Reviews, 2020)
This study aims to determine the strategy of the Local Government of Bener Meriah Regency, in this case, what the Tourism Office has done in building halal tourism in Bener Meriah Regency. This research is a descriptive study with the support of qualitative data. Data collection techniques were obtained through in-depth interviews and documentation studies. The determination of informants was obtained by purposive sampling technique. From the research results, it was found that the Regional Government in building halal tourism in Bener Meriah Regency has not been optimal and is fixing everything related to the concept of halal tourism. Qanun Number 06 of 2018 concerning the Medium-Term Regional Government Plan for 2017-2022 through the first mission of the Regent of Bener Meriah Regency has set the policy direction for the development of the concept of halal tourism in Bener Meriah Regency. The sector that is carried out related to the concept of halal tourism has not touched anything in Bener Meriah Regency. The stakeholder understanding of the concept of halal tourism in local government policies is still limited to building tourism objects in Bener Meriah Regency so that in the future there will be evaluations related to policy directions regarding the concept of tourism halal in Bener Meriah Regency.